2010
DOI: 10.1007/s00198-010-1186-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of alendronate sodium and calcitonin on bone–prosthesis osseointegration in osteoporotic rats

Abstract: In osteoporotic conditions, both administration of ALO orally and CT subcutaneously can enhance periprosthesis bone mass and the effects on osseointegration between host bone and prosthesis. Compared with CT, the effect of ALO is more pronounced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
4
29
0
Order By: Relevance
“…Based on previous literature reports using ALN administration in OVX rats [38][39][40], it was anticipated for the present study that administration of ALN three times per week at a concentration of 2 mg/kg body weight/dose to the rats would be sufficient to prevent the OVX-related bone changes to occur. Indeed, no differences were observed in none of the quantified parameters between shOVX and OVX-ALN groups.…”
Section: Discussionmentioning
confidence: 98%
“…Based on previous literature reports using ALN administration in OVX rats [38][39][40], it was anticipated for the present study that administration of ALN three times per week at a concentration of 2 mg/kg body weight/dose to the rats would be sufficient to prevent the OVX-related bone changes to occur. Indeed, no differences were observed in none of the quantified parameters between shOVX and OVX-ALN groups.…”
Section: Discussionmentioning
confidence: 98%
“…3942 Briefly, the two ends of radius were horizontally fixed on the Material Testing System platform (with a span of 2.5 cm between the supports) and a constant vertical compression load (5 mm/min) was applied to the midpoint of the fractured bone until a fracture occurred. The load and displacement data were recorded at 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Bisphosphonates (BF) are the principal pharmaceutical agents for managing osteoporosis by the inhibition of osteoclasts resorption (21). Studies show that, in osteoporotic condition, bisphosphonates can enhance periprosthesis bone mass and the effects on osseointegration between host bone and prosthesis (22). Moreover, some studies have suggested that bisphosphonates may prevent or may be used to treat aseptic loosening (23), or to prevent the decrease in proximal femoral BMD usually seen after hip replacement (24,25).…”
Section: Discussionmentioning
confidence: 99%